Requirement analysis for LAN implementation in KUSZA - Mohd Fadzil Abdul Kadir (2004)
The implementation of LAN technologies in universities and colleges campus area has been applied a few decades ago. Communications networks are core infrastructures for higher education, providing an essential foundation for all electronic teaching, research, library, and administrative services. LAN technology has helped to simplify networking by enabling multiple computer users to simultaneously share resources in a home or business, and is the perfect way to improve data connectivity. Hence, this project is to study the requirement analysis of LAN implementation in Kolej Ugama Sultan Zainal Abidin (KUSZA) concentrating on the new academic buildings which include the technology of the LAN, user community, and the applications for the users to access the campus network.this project also compares the technology between the wired-LAN and wireless LAN that suitable to the KUSZA environment.